Zev, ki zamaje institucijo - Jelesijević, Nenad (Amfiteater (Ljubljana), 2016)
We understand manifestations of muteness in today's capitalist mise en scene - that keeps and encourages the status of exception via mechanisms of management, surveillance, administration, classification and selection - as a consequence of the depoliticisation of life. In the realm of performance, however, such manifestations might mean resistance against the existing. We are not interested in the mute character as a potential stage(d) representation of the excluded ones, but as a factor that can influence the opening of a space in which silenced voices can be heard. Staging the mute character raises a series of questions: How do we open the delimited stage space? How do we establish conditions for the muted voices to be heard, while at the same time avoiding the trap of representation? How do we gain the space-time of speaking? How do we act outside of the institutional paradigm? How do we face the audience's muteness? The mute character might make a rupture in the spectacle's canon of speaking at any cost, which exactly proves the mute character's performative potential that politicises a stage situation, and also takes effect beyond the very performance. We have noticed foundations for thinking the mute character in the context of institutional critique in two performances: Via Negativa's Last Rehearsal for the Generation and Simona Semenič's The Second Time.
Keywords: gledališki liki; nemi liki; občinstvo; samorefleksija; scenske umetnosti; sodobno gledališče